2023
DOI: 10.1136/bmjopen-2022-071228
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 cross-sectional seroprevalence study among public school staff in Metro Vancouver after the first Omicron wave in British Columbia, Canada

Abstract: ObjectiveTo determine the SARS-CoV-2 seroprevalence among school workers within the Greater Vancouver area, British Columbia, Canada, after the first Omicron wave.DesignCross-sectional study by online questionnaire, with blood serology testing.SettingThree main school districts (Vancouver, Richmond and Delta) in the Vancouver metropolitan area.ParticipantsActive school staff enrolled from January to April 2022, with serology testing between 27 January and 8 April 2022. Seroprevalence estimates were compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
1
1
Order By: Relevance
“…In contrast to our analysis, a higher risk of SARS‐CoV‐2 infection has been reported in adults living with children in the United States 34 and the United Kingdom 35 . Other studies in North America have found that SARS‐CoV‐2 infection was no greater among school staff than in the community and that most COVID‐19 cases among students and teachers were acquired outside the school environment 36–38 . One of these studies was conducted in Ontario during the first wave of the pandemic 37 .…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…In contrast to our analysis, a higher risk of SARS‐CoV‐2 infection has been reported in adults living with children in the United States 34 and the United Kingdom 35 . Other studies in North America have found that SARS‐CoV‐2 infection was no greater among school staff than in the community and that most COVID‐19 cases among students and teachers were acquired outside the school environment 36–38 . One of these studies was conducted in Ontario during the first wave of the pandemic 37 .…”
Section: Discussioncontrasting
confidence: 98%
“… 35 Other studies in North America have found that SARS‐CoV‐2 infection was no greater among school staff than in the community and that most COVID‐19 cases among students and teachers were acquired outside the school environment. 36 , 37 , 38 One of these studies was conducted in Ontario during the first wave of the pandemic. 37 As with our cohort, participants in this study were subject to similar community‐based nonpharmaceutical public health interventions so we believe it is appropriate to compare results between studies.…”
Section: Discussionmentioning
confidence: 99%